BUDAYA KONTEMPLASI SUATU KUNCI KEBAHAGIAAN HIDUP (WELL BEING): Dalam Perspektif Psikologi Islami - Sutarjo, Sutarjo (AL-MISBAH (Jurnal Islamic Studies), 2013)
Contemplation becomes a necessity for individuals who want his happiness. Happiness is here not only means happiness lahiriyah alone, but also about the inner happiness that is hard to measure empirically.In this paper the word contemplation more mentioned the term "evaluation" or muhasabah, because the term is more often heard. This paper discusses how an individual effort that happy life (well-being) in this modern era in Islamic psychology perspective.In contemplation of the psychological perspective of Islamic culture can be beneficial for the individual to be more careful of his life. To gain peace of mind, it takes a kind of guidebook in life. So with no manual human steps to be sure, and no way home. This paper describes what a Muslim is supposed to make a guide book in his life in order to achieve well-being